1996
DOI: 10.1088/0953-4075/29/9/028
|View full text |Cite
|
Sign up to set email alerts
|

A measurement of parity non-conserving optical rotation in atomic lead

Abstract: We report a measurement of parity non-conserving (PNC) optical rotation in the vicinity of the 1.279 µm magnetic dipole transition in atomic lead. We obtain a value for the conventional parameter, R = Im E1 PNC / M1 = (−9.80 ± 0.33) × 10 −8 , with limits on the nuclear spin-dependent contribution set by the anapole constant κ a = −2.0 (17.0). The experimental results, when combined with the relevant atomic calculations, lead to a value for the mass of the Z 0 boson or, alternatively, place a limit on physics b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 13 publications
3
22
0
Order By: Relevance
“…Atoms with four valence elections were not much investigated with the precision CI-MBPT method in the literature, with the notable exception being work by Dzuba [6] motivated by the alpha-variation project. Lead is of additional interest to theory due to parity-non-conservation (PNC) fundamental symmetry experiments [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…Atoms with four valence elections were not much investigated with the precision CI-MBPT method in the literature, with the notable exception being work by Dzuba [6] motivated by the alpha-variation project. Lead is of additional interest to theory due to parity-non-conservation (PNC) fundamental symmetry experiments [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The present discussion follows that of [1]. We compare the sign of the PV-induced term in (12) with the sign of the term that depends on the E dc field as well as the sign of the PV-mimicking term b x e y cot θ. We consider the harmonics ratio r 0 of (12) :…”
Section: ζ/β Sign Determinationmentioning
confidence: 98%
“…The situation changed when the Bouchiats [4][5][6] demonstrated that APV effects scale as Z 3 , where Z is the nuclear charge, thus reopening the case for observing them in heavy neutral atoms. Following this discovery, several APV experiments were performed for cesium [7][8][9][10][11], bismuth [12], lead [13,14], thallium [15,16] and ytterbium [17]. New APV experiments are underway or in the planning stage [18][19][20][21][22][23][24][25] (see also the review [26] and references therein), with the aim of attaining a ∼ 0.1% accuracy in 133 Cs.…”
Section: Introductionmentioning
confidence: 99%